L'immigration francophone en milieu minoritaire : pour une démarche audacieuse, coordonnée et renforcée - Comité sénatorial permanent des langues officielles, Sénat du Canada (Comité sénatorial permanent des langues officielles, 2023)

Gaps in knowledge and practices of malaria prevention in Francophone African immigrants in Metropolitan Edmonton - Hanna, Taylor A.; Ahmed, Ali; Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Youssef; Petrick, Ryland; Vincent, Etienne; El Hafid, Mélanie; Hawkes, Michel T.; Ravi, Srilata; Gnidehou, Sedami (Malaria Journal, 2022)
Background Important knowledge gaps exist in the understanding of the management of the risks of imported malaria in Canada among Francophone immigrants from sub-Saharan Africa (FISSA). The aim of this cross-sectional study was to investigate the malaria related-knowledge, attitude and practices (KAP) of FISSA in Edmonton, where these immigrants are in an official minority language situation and the impact of language barriers on these factors. Methods A structured survey was used to examine the KAP of 382 FISSA in the Edmonton area from 2018 to 2019. Fisher’s Exact Test was applied to determine if there were associations between knowledge of malaria and different risk factors. Results Almost all FISSA (97%) had an accurate knowledge of fever as the key symptom of malaria. Interestingly, 60% of participants identified bed nets as a preventive method and only 19% of participants had accurate knowledge of malaria transmission. An accurate knowledge of symptoms was significantly associated with a high perceived risk of contracting malaria [odds ratio (OR) 4.33, 95% confidence interval (CI) 1.07–20.62]. Furthermore, even though 70% of FISSA had a high perceived risk of contracting malaria in endemic regions, only 52% of travellers had a pre-travel medical encounter. Importantly, language was not the predominant reason for not seeking pre-travel medical advice, although 84% of respondents chose French as their official language of preference when seeking medical advice. Having a French-speaking physician was correlated with satisfactory prevention knowledge (OR 1.96, 95% CI 1.16–3.35). With respect to health-seeking behaviour, 88% of respondents with a child < 5 years of age would seek medical care for fever in the child after travel to sub-Saharan Africa (SSA). Conclusion This study highlights that factors other than knowledge, risk assessment, and language might determine the lack of compliance with pre-travel medical encounters. It underscores the need for effective strategies to improve this adherence in minority settings.

Portrait statistique sociosanitaire de la population immigrante de l’Ouest et du Nord - Santé en français (2023)
Le présent document pourra être utile aux parties prenantes de la santé des personnes immigrantes en contexte francophone minoritaire. Il vise à outiller ce public à mieux comprendre certaines dimensions du profil sociodémographique et sociosanitaire des personnes immigrantes en contexte francophone minoritaire. Pour ce faire des statistiques sont présentées sous forme de tableau et de graphique, puis interprétées de manière sommaire.

Barriers to and enablers of attendance at diabetic retinopathy screening experienced by immigrants to Canada from multiple cultural and linguistic minority groups - van Allen, Zack; Dogba, Maman Joyce.; Brent, Michael. H.; Bach, Catherine; Grimshaw, Jeremy. M.; Ivers, Noah. M.; Wang, Xiaoqin.; McCleary, Nicola.; Asad, Sarah.; Chorghay, Zahraa.; Hakim, Hina; Sutakovic, Olivera; et al. (Diabetic medicine, 2020)
Aim To identify barriers to/enablers of attendance at eye screening among three groups of immigrantsto Canada from cultural/linguistic minority groups living with diabetes. Methods Using a patient-oriented research approach leveraging Diabetes Action Canada's patient engagement platform, we interviewed a purposeful sample of people with type 2 diabetes who had immigrated to Canada from: Pakistan (interviews in Urdu), China (interviews in Mandarin) and French-speaking African and Caribbean nations (interviews in French). We collected and analysed data based on the Theoretical Domains Framework covering key modifiable factors that may operate as barriers to or enablers of attending eye screening. We used directed content analysis to code barrier/enabler domains. Barriers/enablers were mapped to behaviour change techniques to inform future intervention development. Results We interviewed 39 people (13 per group). Many barriers/enablers were consistent across groups, including views about harms caused by screening itself, practical appointment issues including forgetting, screening costs, wait times and making/getting to an appointment, lack of awareness about retinopathy screening, language barriers, and family and clinical support. Group-specific barriers/enablers included a preference to return to one's country of birth for screening, the impact of winter, and preferences for alternative medicine. Conclusion Our results can inform linguistic and culturally competent interventions to support immigrants living with diabetes in attending eye screening to prevent avoidable blindness.